The continued existence of preventive detention law in Malaysia: whether terrorism is a justification / Musalmi Kholid, Sendra Mathew Masir and Stella Augustine Druce - Kholid, Musalmi; Masir, Sendra Mathew; Druce, Stella Augustine (2005)
This research is a study on the preventive detention law in Malaysia, namely the Internal Security Act (ISA) 1960 in relation to terrorism and issues revolving around it. Distinct from other studies made on the ISA, this study purports to analyze the Act in response to claims made by the authorities on ISA in post September 11 tragedy in New York. The writers seek to materialize a connection between terrorism threats and the real use of ISA in so far it has been in force as well as finding the real cause of terrorism and what are the options to encounter it. Damages and benefit the Act does will also be identified. The first stage of the study will involve information collecting and a review on it; which is then followed by a qualitative analysis on the subject which will be done through legal analysis and reasoning.